Apoptosis and autophagy in polycystic kidney disease (PKD) - Nowak, Kristen L. (Cell Signal, 2019)
Apoptosis in the cystic epithelium is observed in most rodent models of polycystic kidney disease (PKD) and in human autosomal dominant PKD (ADPKD). Apoptosis inhibition decreases cyst growth, whereas induction of apoptosis in the kidney of Bcl-2 deficient mice increases proliferation of the tubular epithelium and subsequent cyst formation. However, alternative evidence indicates that both induction of apoptosis as well as increased overall rates of apoptosis are associated with decreased cyst growth. Autophagic flux is suppressed in cell, zebra fish and mouse models of PKD and suppressed autophagy is known to be associated with increased apoptosis. There may be a link between apoptosis and autophagy in PKD. The mammalian target of rapamycin (mTOR), B-cell lymphoma 2 (Bcl-2) and caspase pathways that are known to be dysregulated in PKD, are also known to regulate both autophagy and apoptosis. Induction of autophagy in cell and zebrafish models of PKD results in suppression of apoptosis and reduced cyst growth supporting the hypothesis autophagy induction may have a therapeutic role in decreasing cyst growth, perhaps by decreasing apoptosis and proliferation in PKD. Future research is needed to evaluate the effects of direct autophagy inducers on apoptosis in rodent PKD models, as well as the cause and effect relationship between autophagy, apoptosis and cyst growth in PKD.